Factors that influencing government servant’s on personal financial planning management: a study at Kota Bharu, Kelantan / Muhammad Izzat Yahya - Yahya, Muhammad Izzat (2013)
The purpose of this study was to investigate the factors which could influence government servants on personal financial planning management at the area of Kota Bharu, Kelantan. The objective is to identify the relationship between independent variables which is personal income, level of education, retirement planning and investment planning with dependent variables which is personal financial planning management. The sample comprised 120 of government servants were collected by using simple random sampling at the Menara Perbadanan and Wisma Persekutuan, Kota Bharu. In order to determine the significance relationship between those variables, this study has used regression analysis which comprised of ANOVA, coefficient of correlation (R), coefficient of determination (R2), multiple regression model and also Durbin Watson statistic. This study also used hypothesis testing by using P-Value approach in determining which of the null hypothesis will be reject or accept. The results of the findings state that personal income and retirement planning has a significance relationship between the variables. Whereas, level of education and investment planning does not have any significant relationship between the variable